2010
DOI: 10.1097/prs.0b013e3181d4fdc5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Ischemia-Reperfusion Injury in In Vitro and In Vivo Models of Intestine Free Tissue Transfer

Abstract: Hydrogen sulfide significantly attenuates ischemia-reperfusion injury in intestinal tissue in vitro and in vivo. These results have significant implications for enteric free tissue transfers and other gastrointestinal procedures in which ischemic intervals may be anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…*P \ 0.05, comparison between 2VO group and 2VO-NaHS group. # P \ 0.05, comparison between sham group and 2VO group production may be of therapeutic benefit in the treatment of ischemia-induced organ injury [3,[39][40][41]. However, less investigation was about the effect of H 2 S on brain ischemia in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*P \ 0.05, comparison between 2VO group and 2VO-NaHS group. # P \ 0.05, comparison between sham group and 2VO group production may be of therapeutic benefit in the treatment of ischemia-induced organ injury [3,[39][40][41]. However, less investigation was about the effect of H 2 S on brain ischemia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S-mediated cytoprotection was in connection with an improved balance between reduced GSH and oxidized glutathione (GSSG), an attenuated formation of lipid hydroperoxides, and an increased expression of thioredoxin-1 (Trx-1) [17]. Previous studies demonstrated that H 2 S significantly decreased apoptosis in vivo and vitro in the setting of ischemia injury [27,39]. H 2 S inhibited the progression of apoptosis after I/R injury by increasing the protein expression of heat shock protein (HSP-90) and Bcl-2 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the protective effect of NaHS is less evident at higher doses than at lower doses, as seen in previous studies. [15][16][17] According to our results, we propose that the most beneficial NaHS concentrations are 0.1 to 100 μM for adipose tissue.…”
Section: Discussionmentioning
confidence: 67%
“…For in vitro cell culture studies for hypoxia, 1% O 2 levels have been used. 16,17 Similar to the literature, the hypoxic conditions in our study were set to 1% O 2 for the mature adipocyte and adipose-derived mesenchymal cell cultures. By using a special incubator, the gas levels could be set and maintained at constant levels during the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation